Adherence to treatment guidelines in a university hospital: Exploration of facts and factors (Bangladesh Journal of Pharmacology, 2014)
The present study was conducted to evaluate the adherence to treatment guidelines in Bangabandhu Sheikh Mujib Medical University. The study assessed the awareness of prescribers, adherence to treatment guidelines and reasons for non-adherence. A questionnaire survey was conducted followed by a retrospective medical review and in-depth interview. The study revealed that 60.9% of key prescribers are aware of Treatment Guidelines. In pediatric patients, adherence was highest in neonatal sepsis (71.7%) and lowest in bronchial asthma (3.3%) and pneumonia (3.3%). In adult patients, adherence was highest in rheumatoid arthritis (100%) and lowest in bronchial asthma (13.3%). Adherence was 29.5% and 52.7% in pediatric and adult patients respectively and difference was highly significant (p